THE PRACTICE OF WALKING: CONTROL AND PREVENTION OF ARTERIAL HYPERTENSION IN PEOPLE WALKING IN FORMOSA DA SERRA NEGRA-MA - Asunção Santos, Aurélio; de Melo Oliveira, Bruno (Health and Society, 2022)
The physical exercise today has expanded increasingly in Brazil and in the world today with so many technologies that make us sedentary and somewhat indisposed to any exertion, there are alternative means of exercise as the practice of walking, which can It is made by any individual. The city of Formosa Black Mountain - MA is an example of this type of physical activity has motivated more and more people, and attracting large number of participants every day. Through quantitative research also with a qualitative approach, we seek information on the perception of practitioners on the risk of hypertension, the importance of walking as well as the needs that led them to practice the exercise. The presentation of the results of the research promotes a reflection about the importance of professional supervision in regular exercise practice. We conclude that hikers have no professional monitoring and therefore do not reach effectively the desired objectives. The walks held without guidance of physical education teachers or a health professional has positive and negative implications for health practitioners. With the completion of this study we concluded that the presence of a professional physical education or health is essential for the practice of walking to be truly effective. The results were presented by graphic analysis. We believe that the next job can improve the way of thinking and living of formoserranegrense citizens.